2015
DOI: 10.1166/jnn.2015.10617
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Nanomaterials in Radiotherapy for Malignant Tumors

Abstract: Malignant tumors are tremendous heath problems facing by the medical world. In order to achieve the purpose of curing malignant tumor, numerous therapeutic strategies have been developed. Radiotherapy is one of the main therapeutic strategies for malignant tumors. Current imaging strategies cannot display exact infiltrating margins, radio-resistance generated by irradiated tissue, and intercurrent damage to healthy tissues during radiotherapy. Therefore, novel strategies to solve these problems are urgently ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Several studies were related to the design of various types of nanostructured scaffolds that could allow the regeneration of different type of tissues [27,28,29]. In addition, it was reported that these materials and matrices have been compared and evaluated for their better biocompatibility and efficacy in supporting the damaged tissue [30,31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies were related to the design of various types of nanostructured scaffolds that could allow the regeneration of different type of tissues [27,28,29]. In addition, it was reported that these materials and matrices have been compared and evaluated for their better biocompatibility and efficacy in supporting the damaged tissue [30,31,32]. …”
Section: Discussionmentioning
confidence: 99%
“…For EBRT, radiation beams such as high-energy x-rays, electron or proton beams from outside the body are placed directly onto tumors to induce cancer cell death. [2,[4][5][6][7][13][14][15][16] Despite the wide use of RT for cancer treatment, it still has many shortcomings. [7][8][9][10][11][12] While EBRT has been extensively employed for treatment of local solid tumors such as breast, colorectal, esophageal, head and neck, lung, prostate, and brain tumors, RIT can be used to treat both local tumors as well as metastatic tumors spread throughout the body.…”
Section: Doi: 101002/adma201700996mentioning
confidence: 99%
“…Each of these approaches, however, currently has some limitations and challenges that will need to overcome for optimal application. [128][129][130] There are many ways in which these roadblocks can be addressed both synthetically and biologically, with perhaps the most promising route being the co-engineering of AuNCs and …”
Section: Conclusion and Perspectivementioning
confidence: 99%